PERAN PENGASUH DAN KEMANDIRIAN ANAK - Nur Vitasari; Atik Badi'ah (MEDIA ILMU KESEHATAN, 2013)
Background: The role of nurse in guiding, directing and managing the child is required to establish an independent children's personalities. Child's independence is marked by the ability to perform simple daily activities. Independence is not a skill that appears suddenly, but need to be taught to children. The role of nurse is intended to foster the ability of the child's independence from an early age, so it will be able to grow and develop optimally. Objectives: To know the relevance of the role of carer to preschooler’s independence in Aisyiyah Perumnas Condongcatur Yogyakarta Playgroup. Methods: The method used was descriptive correlation with the cross-sectional approach. Samples were obtained by the total sampling technique and hypothesis test was done by Kendall’s Tau test to know the relevance of the role of carer to preschooler’s independence at Aisyiyah Perumnas Condongcatur Yogyakarta Playgroup in 2012. Results: (1) The role of carer in fostering independence preschoolers mainly categorized good as many as 50 people (96.2%), (2) preschooler’s independence according to their parents mainly categorized medium as many as 26 children ( 50%), (3) The result of Kendall Tau test obtained coefficient Kendall Tau as much as 0.455 with a significance of 0.000 (sig <0.05). Therefore, there was the relevance of the role of carer to preschooler’s independence in Aisyiyah Perumnas Condongcatur Yogyakarta Playgroup. Conclusion: There is the relevance of the role of carer to preschooler’s independence in Aisyiyah Perumnas Condongcatur Yogyakarta Playgroup. This study recommends that the carers (parents and teachers) can be carers and friends of children with affection, attention and understanding the needs, desires and character of foster children. Key words: The role of carer, preschooler’s independence